Legal Education and Child-Responsive Digital Reporting Systems for School Bullying Victims - Anis Widyawati; Diyah Satya Retnani (The Indonesian Journal of International Clinical Legal Education, 2026)
School bullying remains a significant challenge in educational institutions, affecting children's psychological well-being, academic performance, and access to justice. Despite the existence of legal protection frameworks and anti-bullying policies, many cases remain unreported due to fear of retaliation, limited legal awareness, social stigma, and the absence of child-friendly reporting mechanisms. This study aims to examine the role of legal education as the foundation for developing child-responsive digital reporting systems and to analyze the implementation of SI GETAK as an innovative mechanism for protecting school bullying victims. Employing a qualitative empirical socio-legal approach, the study combines regulatory analysis, literature review, and empirical findings obtained through interviews with educational stakeholders, including school administrators, teachers, students, and local education authorities. The findings reveal that legal education enhances students' understanding of their rights, encourages reporting behavior, and strengthens access to justice for bullying victims. Furthermore, the implementation of SI GETAK demonstrates that digital reporting systems can provide accessible, confidential, and child-friendly channels for reporting bullying incidents while facilitating coordination among schools, parents, counselors, and relevant authorities. Based on these findings, this study proposes a Legal Education-Based Child-Responsive Digital Reporting Framework consisting of five interconnected dimensions: legal education and rights awareness, child-friendly digital reporting access, integrated protection and case management, restorative justice and victim recovery, and institutional accountability and monitoring. The study contributes to the existing literature by integrating legal education, child protection principles, and digital reporting technologies into a comprehensive framework that strengthens child protection and promotes safer educational environments in the digital era.